Clinical presentations, risk factors and outcomes of ceftazidime‐resistant Gram‐negative endophthalmitis. (11th October 2016) - Dave, Vivek Pravin; Pathengay, Avinash; Nishant, Kumar; Pappuru, Rajeev R; Sharma, Savitri; Sharma, Pranjali; Narayanan, Raja; Jalali, Subhadra; Mathai, Annie; Das, Taraprasad
Abstract: Background: To describe the clinical features and outcomes of patients diagnosed with ceftazidime‐resistant Gram‐negative endophthalmitis and the role of intravitreal imipenem in these cases. Design: Retrospective consecutive interventional case series at a tertiary eye care centre in South India. Participants: Consecutive cases of ceftazidime‐resistant Gram‐negative endophthalmitis from April 2010 to December 2014. Fifty‐six cases diagnosed during this time period were included. Methods: All cases were managed with vitreous biopsy/vitrectomy, microscopy and undiluted vitreous culture, antimicrobial susceptibility of bacterial isolates and received intravitreal antibiotics. Main Outcome Measures: Anatomic and visual outcome of these cases, antimicrobial susceptibility pattern of intravitreal imipenem and outcome of cases injected with it. Results: Commonest presentation was acute endophthalmitis following cataract surgery (27 eyes, 48.21%). Pseudomonas aeruginosa was isolated in 33 eyes (58.93%; 95% CI 46.05–71.81%). Nineteen eyes (34%; 95% CI 21.59–46.41%) developed phthisis; 14 eyes (25%; 95% CI 13.66–36.34%) had vision <20/200; 17 eyes (30.35%; 95% CI 18.31–42.39%) eyes had an ambulatory vision >20/200 (logMAR 1); 6 eyes (10.71%; 95% CI 2.61–18.81%) had a reading vision >20/40 (logMAR 0.3). Trend was towards better anatomic (72.73% vs . 40%) ( P = 0.05) and visual improvement in the imipenem group (logMAR 3.94 + 0.21 to 2.43 + 1.4; P = 0.002), as compared with non‐imipenem group (logMAR 2.99 + 1.3 to 2.55 + 1.4; P = 0.13). Conclusions: Outcome of ceftazidime‐resistant Gram‐negative endophthalmitis is poor. P . aeruginosa is the commonest isolated organism. All cases were sensitive to imipenem. There was a trend towards better anatomic outcome in imipenem‐treated eyes.